Senescence: a double-edged sword in beta-cell health and failure? - Varghese, Sneha S.; Dhawan, Sangeeta (Frontiers in Endocrinology, 2023)
Cellular senescence is a complex process marked by permanent cell-cycle arrest in response to a variety of stressors, and acts as a safeguard against the proliferation of damaged cells. Senescence is not only a key process underlying aging and development of many diseases, but has also been shown to play a vital role in embryogenesis as well as tissue regeneration and repair. In context of the pancreatic beta-cells, that are essential for maintaining glucose homeostasis, replicative senescence is responsible for the age-related decline in regenerative capacity. Stress induced premature senescence is also a key early event underlying beta-cell failure in both type 1 and type 2 diabetes. Targeting senescence has therefore emerged as a promising therapeutic avenue for diabetes. However, the molecular mechanisms that mediate the induction of beta-cell senescence in response to various stressors remain unclear. Nor do we know if senescence plays any role during beta-cell growth and development. In this perspective, we discuss the significance of senescence in beta-cell homeostasis and pathology and highlight emerging directions in this area that warrant our attention.